Dampak Pandemi Covid-19 Terhadap Pelayanan ANC Terpadu Ditinjau dari Sikap dan Dukungan Keluarga Di Wilayah Kerja Puskesmas Dau Malang - Woro Tri Utami; Wiqodatul ummah (Universitas Tribhuwana Tunggadewi, 2022)
Integrated antenatal care is provided to all pregnant women with the aim of detecting as early as possible any abnormalities/disorders/diseases suffered by pregnant women. The coverage of Integrated ANC services has decreased during the covid-19 pandemic. External factors are the mother's attitude and family support. The purpose of this study was to determine the effect of the COVID-19 pandemic on integrated ANC services in terms of attitudes and family support at the Dau Health Center, Malang Regency. This research method uses an analytical survey method with a cross sectional approach. The population in this study were all pregnant women who were examined in the Dau Malang Health Center Work Area, namely 30 pregnant women, the sample in this study was obtained by Total Sampling of 30 pregnant women. The analysis used is the Chi-Square test. The results of the analysis based on the output results are known from the chi-square test between Integrated ANC Services in terms of Mother's Attitude with a value of (0.000) (0.05). While the test between Integrated ANC Services in terms of family support with a value of (0.000) (0.05). There is a relationship between Integrated ANC Services in terms of mother's attitude and family support at Dau Malang Health Center